AN ANALYSIS OF ILLOCUTIONARY ACTS AND IMPLICATURES IN UNDERSTANDING TOEFL SHORT CONVERSATION - Desi Tri Cahyaningati (JURNAL SOSIAL HUMANIORA (JSH), 2012)
Listening comprehension is found to be among the most difficult tasks for thelearners due to several reasons. Mostly, test-takers find difficulty in interpretingthe intended meaning of the utterances in the TOEFL examination. To understandthe intended meaning which is implied in and beyond the utterance itself, the testtakers must have background knowledge of the context of the utterances. Basedon the problems faced by the test takers above, this study gives some solutions inunderstanding the short conversation in TOEFL so they can draw conclusion ofthe intended meanings. The writer uses illocutionary acts and implicatures inanalyzing the problems found in TOEFL short conversation. Based on theanalysis, this study concludes that TOEFL short conversations consist of fourillocutionary acts classifications of five. There are Directive, Expressive,Assertive and Commisive. Most of the illocutionary acts found in TOEFL shortconversations are directive, assertive and expressive. Meanwhile, Commisive issometimes found in TOEFL short conversations. This study also gets the data ofthe implicatures on the utterance in TOEFL short conversations. There are someimplicatures that can help the test takers in understanding the intended meaningof the utterance in TOEFL short conversations. Thus to understand the intendedmeaning on the utterances, the test takers can interpret the meaning by applyingthe illocutionary act theory and the implicatures. The illocutionary will help thetest taker to identify the types of the utterance and then can understand theintended meaning of the utterance. The implicatures will explain what a speakercan imply, suggest, or mean, as different from what the speaker literally says.